2014
DOI: 10.3109/09638288.2014.962109
|View full text |Cite
|
Sign up to set email alerts
|

Communication intervention in Rett syndrome: a survey of speech language pathologists in Swedish health services

Abstract: Communication aids were reported to have a positive influence on communicative functions. Swedish SLP services followed best practice in several aspects, but there are areas with potential for development. Tools and best practice guidelines are needed to support SLPs in the AAC process for clients with Rett syndrome. [Box: see text].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 62 publications
0
21
0
2
Order By: Relevance
“…For example, a survey study of individuals with ALS in Germany found a rejection rate of 48% by health insurance institutions concerning communication devices such as eye-gaze controlled computer [32]. A survey in the Netherlands on families with a child with Rett syndrome [33] and a study of speech-language therapists in Sweden who support individuals with Rett syndrome [34] show that not all of these individuals have an opportunity to try eye-gaze technology to see if they may benefit from its use.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a survey study of individuals with ALS in Germany found a rejection rate of 48% by health insurance institutions concerning communication devices such as eye-gaze controlled computer [32]. A survey in the Netherlands on families with a child with Rett syndrome [33] and a study of speech-language therapists in Sweden who support individuals with Rett syndrome [34] show that not all of these individuals have an opportunity to try eye-gaze technology to see if they may benefit from its use.…”
Section: Discussionmentioning
confidence: 99%
“…Without the ability to speak or to adeptly use their hands for pointing, typing, or sign language, expressive language is difficult. Evolving strategies in teaching and augmentative communication technologies have resulted in fresh perspectives and attitudes about what individuals with RTT can achieve [16]. …”
Section: Genetics and Clinical Features Of Rttmentioning
confidence: 99%
“…New technologies applied to communication therapies and rehabilitation (e.g. eye tracking-based devices; [28]) are also effective and promote better development and QoL.…”
Section: Rtt Diagnosis Clinical Features and Managementmentioning
confidence: 99%
“…The latter include aggressive nutritional management, with particular attention to adequate caloric intake and calcium and vitamin D metabolism, prevention of gastrointestinal and orthopedic complications, as well as the entire range of rehabilitation therapies. Some of these RTT-specific approaches have been formalized as management guidelines [24,2832], with others still under development.…”
Section: Rtt Diagnosis Clinical Features and Managementmentioning
confidence: 99%